TAFSIR AYAT-AYAT MUSIBAH AHSIN SAKHO MUHAMMAD - Maemunah, Maya; Mursyid, Ali (Asosiasi Dosen PTKIS Indonesia, 2022)
The study of the interpretation of the verses related to disaster in this article is important for the reasons; First, the theme of disaster is always relevant, disaster always exists throughout human life. Second, Indonesia is a disaster-prone country. Third, these two years, there is still a prolonged Covid-19 outbreak. Fourth, born from the work of an Indonesian expert in the Qur'an, namely Dr. KH. Ahsin Sakho Muhammad, entitled